Il postmoderno è antiquato. La tecnica come soggetto della storia in Günther Anders - Rasini, Vallori (B@belonline, 2024)
In the same years that Jean-François Lyotard was introducing a significant shift in the interpretation of reality by publishing his seminal work on postmodernism, on the fall of grand metaphysical narratives, on the decline of totalising rationality and on the profound crisis of utopias, Günther Anders was contemplating a far more radical transformation in the trajectory of human cultural evolution: the “change of the subject of history” and the potential end of human history. The advent of the technological era not only brings with it a change of the paradigm for interpreting reality in the course of history, but also overturns the “ontological” condition of man, who has now become “ahistorical”. This places technology at the centre of history as its sole subject, rendering the very idea of a postmodern era antiquated.